Continuidade e descontinuidade: a lógica do fragmento na filosofia de Walter Benjamin - Roque, Joaquim Iarley Brito (2013)
This paper aims to present the philosophical itinerary followed by Walter Benjamin (1892-1940) highlighting how their "gnoseology" aims to overcome the systematic deductive logic and science and achieve fragmentary logic of current reality without cover all elements that form. The Thinker launches in the introduction-epistemological critique of his work Origin of German Baroque Drama and its Cheap concepts like allegory, monadology, assembly, presentation, among others, in a philosophical perspective that in an innovative and original attempts to highlight the need for we raise questions regarding the primacy of fragmentary on systematic within the methods and philosophical theories of our time. Emphasizing the particularities of such epistemological proposal, and how it applies in all of his philosophy present how his criticism is directed to the positivism, historicism, and especially the philosophical conceptions derived from the absolute idealism. Against such a perspective thinker applies the logic of the fragment, the discontinuity in the construction of his Theses on the Philosophy of History is emerging as highlighting the need to establish a philosophy contrary to procedure and logical-deductive mathematical for these are held in a summarized and didactic, leaving aside the problem of singular expression. Finally, the present work aims to demonstrate how the philosophical method Benjamin is based on a presentation called contemplative truth from a discontinuous and intentional setting in which phenomena are saved without losing their distinctiveness.